Implementasi Alokasi Dana Desa dalam Upaya Pembangunan Ekonomi di Desa Bonjeruk Kecamatan Jonggat Kabupaten Lombok Tengah - fatahollah, Nabila; Himawan Sutanto; Irwan Suriadi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This study aims to examine the implementation of the Village Fund Allocation (ADD) in Bonjeruk Village, Jonggat District, Central Lombok Regency, in relation to economic development and its contribution to improving community welfare. The research employed a quantitative approach with data collection techniques were carried out through documentation and brief interviews, which served as supporting data to clarify several pieces of information derived from the quantitative dataset. The data were analyzed using descriptive quantitative techniques, including the presentation of tables, percentages, and data distributions to illustrate the implementation of the Village Fund Allocation (ADD). The results show that the implementation of ADD in Bonjeruk Village is predominantly directed toward physical development, particularly infrastructure improvements that facilitate community economic activities, while non-physical (empowerment) programs remain limited. Approximately 70% of the budget is focused on physical development, with community participation being relatively high during the planning stage but low during the supervision stage. The contribution of ADD can be seen in improved economic accessibility, the role of the Village-Owned Enterprise (BUMDes) in supporting local businesses, and support for social programs such as Direct Cash Assistance (BLT), youth activities, and tourism awareness groups.